1984
DOI: 10.1113/jphysiol.1984.sp015245
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐and post‐junctional effects of tubocurarine and other nicotinic antagonists during repetitive stimulation in the rat.

Abstract: 6. We conclude that tubocurarine and erabutoxin b reduce the e.p.c. amplitude

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 49 publications
10
71
0
Order By: Relevance
“…Nicotinic antagonists such as tubocurarine (Liley & North, 1953;Hubbard & Wilson, 1973) and pancuronium (Blaber, 1973) cause such a rundown and in the case of tubocurarine, this rundown has since been shown to be mediated prejunctionally (Magleby et al, 1981;Gibb & Marshall, 1984). In contrast, erabutoxin b does not produce rundown (Gibb & Marshall, 1984) and trimetaphan, produces rundown by a use-dependent block of the receptor activated ion channel (Gibb & Marshall, 1984). Of the drugs used in this study, tubocurarine, pancuronium and hexamethonium have all been shown to be capable ofblocking the receptor-activated ion channel at the frog neuromuscular junction, although in the cases of tubocurarine and pancuronium, only at concentrations around 10 times higher than were used in this study (Lambert et al, 1983 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinic antagonists such as tubocurarine (Liley & North, 1953;Hubbard & Wilson, 1973) and pancuronium (Blaber, 1973) cause such a rundown and in the case of tubocurarine, this rundown has since been shown to be mediated prejunctionally (Magleby et al, 1981;Gibb & Marshall, 1984). In contrast, erabutoxin b does not produce rundown (Gibb & Marshall, 1984) and trimetaphan, produces rundown by a use-dependent block of the receptor activated ion channel (Gibb & Marshall, 1984). Of the drugs used in this study, tubocurarine, pancuronium and hexamethonium have all been shown to be capable ofblocking the receptor-activated ion channel at the frog neuromuscular junction, although in the cases of tubocurarine and pancuronium, only at concentrations around 10 times higher than were used in this study (Lambert et al, 1983 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that the binding site involved in the production of fade could be a presynaptic AChR [2][3][4][5][6][7][8]. In evaluation of our data it is important to underscore the fact that all efforts to detect interaction or binding of o~-toxins to putative presynaptic ACh receptors of any type have been unsuccessful [11].…”
Section: Discussionmentioning
confidence: 99%
“…Reports that or-toxins do not cause fade as does curare [5,6,9,10] and do not bind to the presynaptic nerve terminal [11] have been cited as support for this theory [2,5,9]. It has been reported that unlike curare, the or-toxin from Laticauda semifasciata does not cause a fade in end-plate currents [5], nor does it bring about tetanic fade in the isolated rat diaphragm [6]. Similarly, it has been reported that a,-bungarotoxin from Bungarus multicinctus does not cause tetanic fade in the tibialis anterior muscle of the anaesthetized cat [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A block by non-depolarizing NBAs would lead to a progressive decrease in the amount of ACh released per stimulus during TOF stimulation, accounting for the TOF fade phenomenon. 8,17,18 Based on this mechanism, differences among drugs in the production of the TOF fade can be accounted for by different affinities for prejunctional receptors, i.e. , the greater the affinity, the greater the TOF fade.…”
Section: A B Cmentioning
confidence: 99%